Network Security - Huang, Scott C.-H; MacCallum, David; Du, Ding-Zhu (Springer US : Imprint: Springer, 2010)
This volume highlights and addresses several key challenges in the area of Network Security. Covered is a comprehensive array of topics including secure metering, group key management, denial-of-service attacks, routing and intrusion detection and many more. The book contains eleven peer reviewed chapters, authored by prominent researchers from around the globe. Although the topics do not cover every aspect of network security, they do represent the most fundamental and practical techniques. Network Security should be of interest to researchers and network security experts in the field.